1980
DOI: 10.1530/acta.0.0940089
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal profile of the cycle in 68 normally menstruating women

Abstract: Recent molecular and morphological systematic investigations revealed that the cacti are most closely related to Anacampseroteae, Portulaca and Talinum of the family Portulacaceae (ACPT clade of suborder Portulacineae). A combined analysis of ndhF, matK, and nad1 sequence data from the chloroplast and the mitochondrial genomes indicates that the tribe Anacampseroteae is the sister group of the family Cactaceae. This clade, together with Portulaca, is well characterized by the presence of axillary hairs or scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(156 citation statements)
references
References 0 publications
14
139
2
1
Order By: Relevance
“…A similar pattern of results was also evident for female, but not male, facial attractiveness. Given strong associations between estradiol-to-progesterone ratio and conception risk (Landgren et al, 1980;Baird et al, 1991), these results are consistent with other research suggesting that women's attraction to masculine men is greater when conception risk is high (see Gildersleeve et al, 2014 for discussion). Our results also suggest that women may be more sensitive to female attractiveness at this time.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A similar pattern of results was also evident for female, but not male, facial attractiveness. Given strong associations between estradiol-to-progesterone ratio and conception risk (Landgren et al, 1980;Baird et al, 1991), these results are consistent with other research suggesting that women's attraction to masculine men is greater when conception risk is high (see Gildersleeve et al, 2014 for discussion). Our results also suggest that women may be more sensitive to female attractiveness at this time.…”
Section: Discussionsupporting
confidence: 86%
“…Estradiol-to-progesterone ratio and testosterone may have different effects on responses to male faces because, while estradiol-to-progesterone ratio is a very good predictor of conception risk across the menstrual cycle (Landgren et al, 1980;Baird et al, 1991), testosterone may be more sensitive to situational factors related to competition for resources and mating (van Anders et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on this matter, it is important to note that Cobey et al (2013) observed no difference in reported intrasexual competitiveness between the late-follicular and mid-luteal phases of the menstrual cycle in women with natural menstrual cycles and that we found no evidence that women's intrasexual competitiveness tracked changes in their estradiol-toprogesterone ratio, a correlate of women's fertility (Baird et al, 1991;Landgren et al, 1980). Further work is needed to explore these issues.…”
Section: Discussionmentioning
confidence: 71%
“…To test for within-subject effects of hormone levels on reported intrasexual competitiveness and jealousy, scores on the intrasexual competitiveness and jealousy scales were entered as the dependent variable at the test session level and values for salivary estradiol, progesterone, testosterone, estradiolto-progesterone ratio, and cortisol were simultaneously entered as predictors, again at the test session level. Estradiol-to-progesterone level was included in our analyses in addition to estradiol and progesterone because it is positively correlated with fertility in women not using hormonal contraceptives (Baird et al, 1991;Landgren et al, 1980). Cortisol was included in our analyses in addition to testosterone because of previous work demonstrating that engaging in intrasexual competition increases women's cortisol and testosterone levels (Bateup et al, 2002;Casto & Edwards, in press).…”
Section: Analysesmentioning
confidence: 99%